Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Let's solve the equation step-by-step:
Given equation:
[tex]\[ \frac{x^2 - x - 6}{x^2} = \frac{x - 6}{2x} + \frac{2x + 12}{x} \][/tex]
Step 1: Identify the least common denominator (LCD) for the fractions.
The denominators are [tex]\(x^2\)[/tex], [tex]\(2x\)[/tex], and [tex]\(x\)[/tex]. The least common denominator is [tex]\(2x^2\)[/tex].
Step 2: Multiply each term on both sides of the equation by the LCD ([tex]\(2x^2\)[/tex]) to clear the fractions.
Multiplying each side:
[tex]\[ 2x^2 \cdot \frac{x^2 - x - 6}{x^2} = 2x^2 \cdot \left(\frac{x - 6}{2x} + \frac{2x + 12}{x}\right) \][/tex]
This simplifies to:
[tex]\[ 2(x^2 - x - 6) = 2x^2 \cdot \frac{x - 6}{2x} + 2x^2 \cdot \frac{2x + 12}{x} \][/tex]
Step 3: Simplify each term.
Starting with the left-hand side:
[tex]\[ 2(x^2 - x - 6) = 2x^2 - 2x - 12 \][/tex]
On the right-hand side, simplify each multiplication:
[tex]\[ 2x^2 \cdot \frac{x - 6}{2x} = x(x - 6) = x^2 - 6x \][/tex]
[tex]\[ 2x^2 \cdot \frac{2x + 12}{x} = 2x(2x + 12) = 4x^2 + 24x \][/tex]
Adding these together:
[tex]\[ x^2 - 6x + 4x^2 + 24x = 5x^2 + 18x \][/tex]
Now the equation is:
[tex]\[ 2x^2 - 2x - 12 = 5x^2 + 18x \][/tex]
Step 4: Move all terms to one side to set the equation to zero:
[tex]\[ 2x^2 - 2x - 12 - 5x^2 - 18x = 0 \][/tex]
Combine like terms:
[tex]\[ -3x^2 - 20x - 12 = 0 \][/tex]
Step 5: To find the solutions for [tex]\(x\)[/tex], solve the quadratic equation [tex]\(-3x^2 - 20x - 12 = 0\)[/tex].
This quadratic equation can be solved using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\(a = -3\)[/tex], [tex]\(b = -20\)[/tex], and [tex]\(c = -12\)[/tex].
First, calculate the discriminant ([tex]\(\Delta\)[/tex]):
[tex]\[ \Delta = b^2 - 4ac = (-20)^2 - 4(-3)(-12) = 400 - 144 = 256 \][/tex]
Since the discriminant is positive, we will have two real solutions:
[tex]\[ x = \frac{-(-20) \pm \sqrt{256}}{2(-3)} = \frac{20 \pm 16}{-6} \][/tex]
Now calculate the two solutions:
[tex]\[ x = \frac{20 + 16}{-6} = \frac{36}{-6} = -6 \][/tex]
[tex]\[ x = \frac{20 - 16}{-6} = \frac{4}{-6} = -\frac{2}{3} \][/tex]
Thus, the solutions are:
[tex]\[ x = -6 \quad \text{and} \quad x = -\frac{2}{3} \][/tex]
Finally, we should verify whether these values do not make any of the denominators in the original equation zero.
For [tex]\(x = -6\)[/tex]: The denominators [tex]\(x^2\)[/tex], [tex]\(2x\)[/tex], and [tex]\(x\)[/tex] are not zero.
For [tex]\(x = -\frac{2}{3}\)[/tex]: The denominators [tex]\(x^2\)[/tex], [tex]\(2x\)[/tex], and [tex]\(x\)[/tex] are not zero.
Thus, the solutions [tex]\(x = -6\)[/tex] and [tex]\(x = -\frac{2}{3}\)[/tex] are valid solutions to the equation.
Given equation:
[tex]\[ \frac{x^2 - x - 6}{x^2} = \frac{x - 6}{2x} + \frac{2x + 12}{x} \][/tex]
Step 1: Identify the least common denominator (LCD) for the fractions.
The denominators are [tex]\(x^2\)[/tex], [tex]\(2x\)[/tex], and [tex]\(x\)[/tex]. The least common denominator is [tex]\(2x^2\)[/tex].
Step 2: Multiply each term on both sides of the equation by the LCD ([tex]\(2x^2\)[/tex]) to clear the fractions.
Multiplying each side:
[tex]\[ 2x^2 \cdot \frac{x^2 - x - 6}{x^2} = 2x^2 \cdot \left(\frac{x - 6}{2x} + \frac{2x + 12}{x}\right) \][/tex]
This simplifies to:
[tex]\[ 2(x^2 - x - 6) = 2x^2 \cdot \frac{x - 6}{2x} + 2x^2 \cdot \frac{2x + 12}{x} \][/tex]
Step 3: Simplify each term.
Starting with the left-hand side:
[tex]\[ 2(x^2 - x - 6) = 2x^2 - 2x - 12 \][/tex]
On the right-hand side, simplify each multiplication:
[tex]\[ 2x^2 \cdot \frac{x - 6}{2x} = x(x - 6) = x^2 - 6x \][/tex]
[tex]\[ 2x^2 \cdot \frac{2x + 12}{x} = 2x(2x + 12) = 4x^2 + 24x \][/tex]
Adding these together:
[tex]\[ x^2 - 6x + 4x^2 + 24x = 5x^2 + 18x \][/tex]
Now the equation is:
[tex]\[ 2x^2 - 2x - 12 = 5x^2 + 18x \][/tex]
Step 4: Move all terms to one side to set the equation to zero:
[tex]\[ 2x^2 - 2x - 12 - 5x^2 - 18x = 0 \][/tex]
Combine like terms:
[tex]\[ -3x^2 - 20x - 12 = 0 \][/tex]
Step 5: To find the solutions for [tex]\(x\)[/tex], solve the quadratic equation [tex]\(-3x^2 - 20x - 12 = 0\)[/tex].
This quadratic equation can be solved using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\(a = -3\)[/tex], [tex]\(b = -20\)[/tex], and [tex]\(c = -12\)[/tex].
First, calculate the discriminant ([tex]\(\Delta\)[/tex]):
[tex]\[ \Delta = b^2 - 4ac = (-20)^2 - 4(-3)(-12) = 400 - 144 = 256 \][/tex]
Since the discriminant is positive, we will have two real solutions:
[tex]\[ x = \frac{-(-20) \pm \sqrt{256}}{2(-3)} = \frac{20 \pm 16}{-6} \][/tex]
Now calculate the two solutions:
[tex]\[ x = \frac{20 + 16}{-6} = \frac{36}{-6} = -6 \][/tex]
[tex]\[ x = \frac{20 - 16}{-6} = \frac{4}{-6} = -\frac{2}{3} \][/tex]
Thus, the solutions are:
[tex]\[ x = -6 \quad \text{and} \quad x = -\frac{2}{3} \][/tex]
Finally, we should verify whether these values do not make any of the denominators in the original equation zero.
For [tex]\(x = -6\)[/tex]: The denominators [tex]\(x^2\)[/tex], [tex]\(2x\)[/tex], and [tex]\(x\)[/tex] are not zero.
For [tex]\(x = -\frac{2}{3}\)[/tex]: The denominators [tex]\(x^2\)[/tex], [tex]\(2x\)[/tex], and [tex]\(x\)[/tex] are not zero.
Thus, the solutions [tex]\(x = -6\)[/tex] and [tex]\(x = -\frac{2}{3}\)[/tex] are valid solutions to the equation.
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.